تحولات الدار السكني العراقي في العقد الاول من القرن الواحد والعشرين - أريج كريم مجيد السدخان; هالة علاء الدين (Journal of Engineering, 2023)
This research describes Iraqi housing in the first decade of the twenty-first century, taking ALAdhamiya as a model, depending on descriptive method of inductive approach to the study of this decade. By doing the field study for three neighborhood in Adhamiya district. Which takes in consideration the comparison between housing in the first period of the first decade of the twenty-first century with the second period of this decade: the latest decades of 21th century. And for many aspects involving areas, sizes, forming, direction of opening of housing and the function, to reach the most important transformation of Iraqi housing in the first decade of this century in order to give a picture of the residential fact for this period.